Parallel Histories : Muslims and Jews in Inquisitorial Spain - Amelang, James S., 1952- (Book collections on Project MUSE., 2013)
The distinct religious culture of early modern Spain -- characterized by religious unity at a time when fierce civil wars between Catholics and Protestants fractured northern Europe -- is further understood through examining the expulsion of the Jews and suspected Muslims. While these two groups had previously lived peaceably, if sometimes uneasily, with their Christian neighbors throughout much of the medieval era, the expulsions brought a new intensity to Spanish Christian perceptions of both the moriscos (converts from Islam) and the judeoconversos (converts from Judaism). In Parallel Histo.